The role of the police in preventing criminality: Case study of lea-lea police station preventive action - Alisapaka, La Ode; Mayunita, Sry; Inzana, Nur (Geuthèë Institute, Aceh, 2025)
This study discusses the Role of Police in Preventing Crime: A Case Study of Preventive Actions of Lea-Lea Police Sector Office. In order to create a sense of security and peace in every community, the Indonesian National Police is tasked with carrying out police duties throughout the country. The police are one of the state institutions that are at the forefront of protecting the community, and the realization of a situation of security and public order is highly expected by the entire community. This can increase motivation and enthusiasm in working because there is no fear of potential disturbances. The Republic of Indonesia National Police has a major responsibility in preventing violations and crimes, providing public services, and protecting and maintaining order in society. The method used in this study is a qualitative descriptive method. The population and sample in this study were Lea-Lea Police Employees in Baubau City. The results of the study are that the role of the Lea-Lea Police in preventing criminal acts is to provide protection to the community, law enforcement, legal prevention, and fostering public security and order. Inhibiting factors in implementing the prevention of criminal acts are low community/parent participation, witnesses are difficult to ask for information and perpetrators run away.